The role of bamboo plantations in rural development: the case of Anji County, Zhejiang, China - Ruíz Pérez, M.; Zhong, M.; Belcher, B.; Xie, C.; Fu Maoyi; Xie, J. (1999)
Bamboos have often been viewed as inferior products, labeled as the "poor man's timber". Development groups have proposed bamboo production as an opportunity for increasing the wealth of the low-income groups. This paper is a study of the household economy of 200 bamboo farmers in eight township of Anji County in China. The authors decribe the process of transformation of rural China from communes to the household responsibility system, the differentiated rate of development among farmers and the role of bamboo in that change. A multiple regression analysis was carried out to study the factors that influence farmers' incomes and their evolution. A warning is sounded against using bamboo production to target low-income group, as well as relying solely on aggr egated data when drawing conclusions on income disparities in China.